The Effect of Academic Self-Management and Reading Anxiety toward Reading Comprehension - Eka Wilany; Desi Surlitasari Dewi (UICELL, 2017)
As one of required subjects in University level for EFL class, reading should be learned by the students to their own way and strategy so that their reading comprehension has better progress. Unfortunately, reading can be a difficult subject for them even though they are English department students. Internal and external can be the two factors for them in learning it. Academic self-management is one of internal psychological factor defined as learning strategy used by foreign learner to control various factors influenced their learning process specifically reading comprehension. Reading anxiety can be the threats of self-concept caused by limited knowledge and foreign language skill. The objective of this research is to find out the effect of academic self-management and reading anxiety toward English reading comprehension. The researcher uses quantitative research by using expost facto design. Random sampling is chosen as sampling technique in this research and English department students of Riau Kepulauan University in Batam as the population. Instruments used by the researcher are questionnaire to assess the students’ academic self-management and their reading anxiety. Moreover, test is used for measuring the students’ reading comprehension. The data was analyzed by using Two-Way ANAVA and then continues to Tuckey test. The result shows that there was effect of academic self-management and reading anxiety toward the students reading comprehension, the score of Qcount bigger than Qtable (12,22>3,07). Then, it was also found that students reading comprehension having low reading anxiety differ to students having high reading anxiety in which Qcount(3.47)> Q table (2.89). Besides that, students higher reading anxiety having high academic self-management were showed different to students low reading anxiety and having high reading anxiety. It was calculated that Qcount (9.00)> Qtable (3.01). In contrary, it was counted that Qcount (-0.08)<Q table (3.01) means there was no difference students lower academic self-management having low reading anxiety and high reading anxiety in reading comprehension